A randomized controlled trial protocol for persistent physical symptoms associated with indoor environment or chronic fatigue: Effectiveness of video-based functional case conceptualization and web-program for improving quality of life - Selinheimo, Sanna; Keinonen, Katariina; Vuokko, Aki; Liesto, Sanna; Sainio, Markku; Lappalainen, Raimo; Paunio, Tiina (Frontiers in Psychology, 2023)
Introduction: Persistent physical symptoms (PPS) refer to symptoms that cannot be fully explained by structural bodily pathology or by environmental factors. Their impact on daily functioning varies from mild to severe disability. So far, evidence-based treatments for PPS have resulted in only small to moderate effects. Treatment protocols with a stronger orientation toward personalized approaches are needed to improve the efficacy and applicability of treatment. In this study, we aim to assess the effect of an online individual case formulation with an Acceptance and Commitment Therapy (ACT) based on digitalized intervention for PPS. This study is conducted among two focus groups: patients with indoor air-related disabling symptoms and patients with chronic fatigue. Methods and analyses: Using a randomized controlled design (RCT) with two parallel groups in a 1:1 ratio, we will compare individual video-based case formulation with a web-based program based on Acceptance and Commitment Therapy (ACT), combined with treatment as usual, with treatment as usual only. The web-based program consists of ten modules, each lasting one week and including training. The planned sample size is 124 eligible patients without attrition. The primary outcome will be health-related quality of life as measured by the 15D questionnaire. The secondary outcome measures will include questionnaires on psychiatric and physical symptoms, illness perceptions, psychological flexibility and work ability. We will also use national registers to obtain information on the use of health care and social benefits to complete patient-reported outcomes. Data collection began in August 2020 and will continue until 2023. Discussion: This trial will provide information on the effects and usefulness of an online administrated individual case formulation and an ACT-based web-program on PPS. Ethics and dissemination: The Ethics Committee of the Hospital District of Helsinki and Uusimaa, Finland, has granted approval for the study. The results will be published in peer-reviewed journals. Trials registration: Clinicaltrials.gov identifier NCT04532827 preresults.